تطوير الفيديوهات لتعليم التراكب في الفصل الثامن من المدرسة المتوسطة الإسلامية - Kamila, Syifa; Mahyudin, Erta; Susiawati, Wati (Penerbit Minhaj Pustaka, 2025)
This study aims to develop and validate instructional videos for teaching tarkib (Arabic syntax) to eighth-grade students at Islamic junior high schools. The research was motivated by the limited use of interactive audio-visual media and the dominance of traditional teaching methods, which often make abstract grammatical concepts difficult to understand and decrease students’ motivation. The developed videos were designed as a solution to present complex syntax lessons visually and auditorily through the CapCut application. The study adopted a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research stages included needs analysis, instructional design, product development, expert validation, and student testing. Data were collected from material and media experts as well as student response questionnaires. The results indicated that the instructional videos achieved a validity score of 86% from the material expert and 91.5% from the media expert, both in the “excellent” category. In addition, the students’ response reached 78%, showing strong engagement and positive perception. Overall, the developed CapCut-based videos proved to be valid, practical, and effective for enhancing students’ understanding and interest in learning tarkib. The study contributes to integrating digital media into Arabic grammar instruction and provides a model adaptable for Islamic educational contexts.